The Significance of Religious Tolerance for University Students: Its Influence on Religious Beliefs and Happiness - Zuhdiyah Zuhdiyah; Kusumasari Kartika Hima Darmayanti; Nyayu Khodijah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
This study investigates the relationship between religious belief, religious tolerance, and students’ happiness. It aims to explore the moderating effect of religious tolerance on the relationship between religious belief and students’ happiness. The study adopts a quantitative methodology, surveying 734 university students. The data is analyzed using Structural Equation Modelling in Mplus. The results indicate that religious belief influences students’ happiness. Additionally, religious belief influences religious tolerance and happiness positively. Religious tolerance also has a direct effect on happiness. The study highlights the moderating influence of religious tolerance on the association between religious belief and happiness. It also suggests that the level of religious tolerance can influence the effect of religious belief on happiness. In order to increase students' happiness while pursuing a bachelor's degree, the implications of these findings highlight the significance of universities considering and promoting religious tolerance among students.